PENGARUH KOMPENSASI FINANSIAL DAN NON FINANSIAL TERHADAP KOMITMEN KARYAWAN PADA PERUSAHAAN SWASTA DI JAWA TIMUR - Riyadi, Slamet (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2010)
The study  empirically  of  the  research  to  examined  the  effect  of :  1. Financial compensation  toward commmitment, 2.  Non_financial compensation  toward commmitment, and 3. Financial compensation  and Non_financial compensation  toward commmitment. The Population this research come from 86 employeee’s privat company at East Java Regency, there are from services and trading sector, production sector, and construction sector. The respondent to analysis 71 employees or response rate 83%. The statistical data analysis used here is the Statistical Package for the Social Science (SPSS) Version 15.0.  The result indicated that out of the 3 (three) hypotheses proposed, All of them hypotheses can be significantly accepted. 1. The financial compensation  was found to have a significant effect on commmitmen at a = 5% and determination coefficient (R2) =  85,6%, 2. Significantly the non financial compensation  affected commmitment at a = 5% and determination coefficient (R2) =  94,1%, 3. And the finally the financial compensation  and non financial compensation  can be significant effect on commmitment at a = 5% and determination coefficient (R2) =  94,1%. Keywords :   Financial Compensation, Non_Financial Compensation, and  Commmitment